Dielectric elastomer fingers for versatile grasping and nimble pinching - Lau, Gih-Keong (2017)
Boneless soft robotic fingers cannot apply concentrated forces to pinch a delicate object. This letter reports a three-dimensional design of dielectric elastomer fingers with higher flexural stiffness and close to 90° voltage-controllable bending for object gripping and pinching. It makes use of tension arch flexures to elevate a pre-stretched dielectric elastomer actuator (DEA) into a roof shape and thus magnifies the tension-induced moment, 40 times higher than a flat DEA does, to bend a stiff base frame. Such fingers make normally close-grippers to lift a payload 8–9 times their weight. They also make normally open grippers that pinch a highly deformable raw egg yolk.